(untitled) (Baghdad Science Journal, 2022)
Water scarcity is one of the most important problems facing humanity in various fields such as economics, industry, agriculture, and tourism. This may push people to use low-quality water like industrial-wastewater. The application of some chemical compounds to get rid of heavy metals such as cadmium is an environmentally harmful approach. It is well-known that heavy metals as cadmium may induce harmful problems when present in water and invade to soil, plants and food chain of a human being. In this case, man will be forced to use the low quality water in irrigation. Application of natural materials instead of chemicals to remove cadmium from polluted water is an environmental friendly approach. Attention was drawn in this research work to use some natural minerals as zeolite, bentonite and montmorillonite to adsorb cadmium element from polluted water. Various concentrations of cadmium in solutions 10, 30 and 50 ppm were treated with three different ratios of each mineral; 1, 3 and 5% (W/V). The obtained results proved that increasing the ratio of amendments to 5% increased Cd adsorption from solution particularly at 50ppm Cd. Zeolite obtained the highest ratio of adsorption (47.90 ppm), followed by montmorillonite (44.99 ppm) and the lowest was bentonite (38.97 ppm). Therefore, it can be recommended that addition of zeolite is the most favorable material to remove Cd element from polluted water.